NUTRIENT CHARACTERIZATION, BIOGAS AND ELECTRICITY GENERATION POTENTIALS OF ROOT AND TUBER WASTES - Salim, A. A.; Ahmed, A.; Hassan, A. W.; Abdulkadir, J.; Abdullahi, R.; Ityonum, B. I.; Bashir, A. I. (FUDMA JOURNAL OF SCIENCES, 2024)
Rapid population growth and increasing food demand have led to a significant rise in organic waste generation, which has had a negative impact on the environment. However, these wastes can be utilized as substrates for anaerobic digestion (AD) biogas production, providing a sustainable and environmentally friendly waste management solution. The aim of this study was to evaluate the nutrient composition, biogas potential, and electricity generation capacity of root and tuber waste as a feedstock for biogas production. Waste samples were collected from various restaurants in Malumfashi. The nutrient composition of the waste samples was analyzed using standardized AOAC methods, and the biogas potential was estimated using the Baserga model equations. The results revealed that the waste samples had a total solid content of 94.70%, a volatile solid content of 87.60%, a crude protein content of 0.10%, a nitrogen-free extract of 5.1%, a crude fiber content of 5.04%, a crude fat content of 7.1%, and an ash content of 5.3%. The estimated biogas yield from complete degradation of fresh organic matter from roots and tubers was 501m3/ton, with a methane content of 52%. Based on the calorific value of biogas and the efficiency of electrical conversion, the estimated electrical potential was determined to be 1072 kWh/ton. The study recommends the utilization of root and tuber waste as a valuable resource for biogas generation and renewable energy production. Additionally, further research should be conducted to determine the specific biogas production outputs of root and tuber wastes.
Keywords: Anaerobic Digestion; Biogas; Roots; Tuber Wastes; Municipal Solid Waste